NAVIGATING ADOLESCENCE: UNDERSTANDING HEDONISTIC LIFESTYLES AMONG INDONESIAN TEENAGERS - Ferdiansyah; Afriana, Renny; Surtiyoni, Endang (EDUCATIONE, 2024)
During adolescence, teenagers are often influenced by various factors that shape their lifestyle choices. This study investigates the hedonistic lifestyle among "X" students at SMP 16 Palembang, focusing on the impacts of parental influence, financial management, environmental factors, and social dynamics. Employing a qualitative descriptive research method, data were collected through observations, interviews, and documentation. The findings reveal that parental neglect and excessive pocket money contribute to students' consumptive behavior, exacerbated by societal trends and peer pressure. The allure of a hedonistic lifestyle, characterized by materialistic pursuits and gadget dependency, poses risks to students' well-being and social development. Furthermore, the study highlights the need for parental guidance and societal support in promoting balanced lifestyles and responsible behavior among adolescents. These findings underscore the i